Effect of Different Concentrations of Amphiregulin/Neurgulin/ Tumour Necrocis Factor α on in vitro Maturation of Ovine Oocytes - Somashetty, Ramesh H.; Sumanta, Nandi; Venkatesh, Girish K. (Indian Journal of Veterinary Sciences and Biotechnology, 2021)
The objective of the present study was to examine the effect of different concentrations of ovarian peptides Amphiregulin (AREG) or Neuregulin-I (NRG-I) or Tumour necrosis factor (TNF-α) on in vitro maturation of ovine oocytes collected from different sizes of ovarian follicles. Oocytes isolated from different ovarian follicles (large antral follicles (LAFs>4mm), medium antral follicles (MAFs<1 mm) and small antral follicles (SAFs,1-4mm)] were cultured with medium supplemented with different concentrations viz. 0 (control), 5, 10, 25, 50, 100, and 150 ng of either AREG or NRG-I or TNF-α in a carbon dioxide incubator for 24 h. Maturation rate assessment was done based on the degree of expansion (cumulus expansion score) and extrusion of the first polar body. The maturation rate of oocytes was significantly (p<0.05) higher in groups exposed to 50 ng, 100 ng and150 ng of AREG in oocytes isolated from LAFs; 100 ng and150 ng of AREG in oocytes isolated from both MAFs and SAFs. The maturation rate of oocytes isolated from LAFs, MAFs and SAFS was significantly (p<0.05) higher in the groups exposed to 25 ng, 50 ng, 100 ng and 150 ng of NRG-I; 50 ng,100 ng and 150ng of NRG-I, respectively. The maturation rates were significantly (P<0.05) higher in the oocytes cultured with 25 ng of TNF-α in oocytes isolated from both LAFs and MAFs and 5 ng and 10 ng of TNF-α in oocytes isolated from SAFs. The results indicated growth factors AREG/NRG-I/TNF-α improved the oocytes maturation in-vitro.